Pseudomonas aeruginosa serotypes and resistance to antibiotics from wound swabs - Stanković-Nedeljković Nataša; Tiodorović Branislav; Kocić Branislava; Ćirić Vojislav; Milojković Marko; Waisi Hadi (Vojnosanitetski Pregled)
Introduction/Aim. Pseudomonas aeruginosa (P. aeruginosa) is the most common cause of wound infections, following the disruption of the skin or mucous membranes integrity. The aim of this study was to analyze of the presence P. aeruginosa in wound swabs, antibiotics susceptibility testing, determination of the minimum inhibitory concentrations (MICs) of antibiotics, testing of the metallo-β-lactamases (MBLs) production, isolates serotyping and analysis of the most common serotypes resistance. Methods. A total of 90 outpatients and 55 intpatients wound swabs were cultivated. Wound swabs were taken from the patients with wound infections symptoms. Antibiotics susceptibility testing was performed to: meropenem, imipenem, piperacillin-tazobactam, ceftazidime, cefepime, amikacin, gentamicin, netilmicin, ofloxacin, ciprofloxacin and colistin (HiMedia). Polyvalent and monovalent antisera for agglutination (Biorad) were used in P. aeruginosa agglutination. Results. P. aeruginosa was isolated from 36.55% wound swabs (36.66% of the inpatients wounds and 36.36% of the outpatients). The analyzed isolates showed the highest degree of sensitivity to colistin (100%) and meropenem (93.44%) and the lowest to cefepime (19.54%). The majority of the inpatients isolates had 12 μg/mL (28.57%) MIC for piperacillin-tazobactam and 16 μg/mL (28.57%) for the outpatients. The most common MICs for ciprofloxacin were 0.19 μg/mL (31.81%) for the nosocomial isolates, and 0.25 μg/mL (28.57%) for the outpatients’ ones. The most common MICs for amikacin of the nosocomial isolates were 6 μg/ml (40.9%), and for the outpatients ones 4 μg/mL (33.33%). Five (9.43%) isolates produced MBLs. The most common serotypes were P11 (22.64%), P6 (15.09%) and P1 (11.32%). Conclusion. Neither the increased presence of P. aeruginosa was noticed in wounds swabs, nor the antibiotic resistance in the nosocomial isolates compared to those from outpatients. The analyzed isolates had the higest sensitivity to colistin and meropenem, and the lowest to cefepime. [Projekat Ministarstva nauke Republike Srbije, br. TR 31080]